An updated checklist of butterflies (lepidoptera: rhopalocera) from the Fraser’s Hill, Pahang, Malaysia - Norfazliana Ghazali,; Mohd Afiq Aizat Jauhari,; Norela Sulaiman, (Pusat Sistematik Serangga, Universiti Kebangsaan Malaysia, 2018)
A total of 32 species of butterflies from five families, i.e. Nymphalidae, Papilionidae, Pieridae, Lycaenidae and Hesperiidae have been recorded in this study from the Fraser’s Hill, Pahang, Malaysia. There were 21 new added records compared to previous studies that have been done by some researchers. The current checklist of butterflies in Fraser’s Hill is 83 species. The species checklist includes three protected species that were listed under the Wildlife Conservation Act 2010, namely Troides brookiana albescens Rothschild, Troides helena cerberus (C. & R. Felder) and Charaxes bernadus crepax Fruhstorfer.